Host- and Phage-Mediated Repair of Radiation Damage in Bacteriophage T4 - Wallace, Susan S. (1972)
T4+ exhibits increased ultraviolet sensitivity on derivatives of Escherichia coli K12 or B lacking deoxyribonucleic acid (DNA) polymerase I. However, the sensitivity of T4v is not affected by the absence of host DNA polymerase. T4x and T4y also show increased sensitivity on DNA polymerase-deficient strains, but to a lesser extent than observed with wild-type T4. When T4x or T4y, but not T4+, are plated on a double mutant lacking both DNA polymerase and the uvrA gene product, a partial suppression of the polymerase effect is observed. Host ligase appears to be able to suppress to some extent the T4y phenotype but has no effect on wild-type T4 or other T4 mutants. T4xv incubated in E. coli B or B(s-1) in the presence of chloramphenicol (50 μg/ml) shows increased resistance over directly plated irradiated phage. Increased survival under the same conditions was not observed with T4+ or other T4 mutants. The repair of X-ray-damaged T4 was investigated by examining survival curves of T4+, T4x, T4y, T4ts43, and T4ts30. The repair processes were further defined by observing the effects of plating irradiated phage on various hosts including strains lacking DNA polymerase I or polynucleotide ligase. Two classes of effects were observed. Firstly, the x and y gene products seem to be involved in a repair system utilizing host ligase. Secondly, in the absence of host DNA polymerase, phage sensitivity is increased in an unknown manner which is enhanced by the presence of host uvrA gene product.